2022
DOI: 10.3390/insects13020211
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperatures and Hosts on the Life Cycle of Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: The interactions between ambient temperatures and host plants are central to the population dynamics of invasive animal species. Despite significant research into the effects of temperatures, the performance of invasive species is also influenced by host plants. The effects of different temperatures (20, 25, and 30 °C) and host plants (maize, sorghum, and coix seed) were tested on the mortality, development, reproduction, and population parameters of the fall armyworm (FAW), Spodoptera frugiperda (J E Smith) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…S. frugiperda exhibited a higher R0 at 27 °C than at 23°C. Similarly, Chen YC et. al., (2022), found that increased temperature led to significant effects on the population parameters (R0, rm and e rm ) of S. frugiperda.…”
Section: Discussionmentioning
confidence: 83%
“…S. frugiperda exhibited a higher R0 at 27 °C than at 23°C. Similarly, Chen YC et. al., (2022), found that increased temperature led to significant effects on the population parameters (R0, rm and e rm ) of S. frugiperda.…”
Section: Discussionmentioning
confidence: 83%
“…If relevant, the model might be easily extended to include the influence of other environmental variables, such as relative humidity. The model does not consider the influence of different host plant species on the life-history (Chen et al 2022), the dynamics, and the distribution of S. frugiperda (Baloch et al 2020). Another source of uncertainty not considered in the model is represented by variability in the physiological responses associated with different strains of the species that might reach Europe (Sarr et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…FAW larval populations were collected from the corn fields of Luoertang Village (27 • 46 44" N, 107 • 40 41" E), Yanchang Town, Fenggang County, Zunyi City, Guizhou Province, China. Larvae were fed with fresh corn leaves and reared in a climatic chamber with temperature set at 25 ± 2 • C, relative humidity of 70 ± 5%, and photoperiod of 14 light:10 dark as described by Chen et al [26]. Emamectin benzoate technical material (TC), with a purity of 70%, was purchased from Guangxi Tianyuan Biochemical Co., Ltd. (Nanning, China).…”
Section: Insects and Test Pesticidesmentioning
confidence: 99%